Urban planning: the urgent needs to redevelop ex-landfill sites as public parks in Malaysia - Mazifah Simis,; Azahan Awang,; Kadir Arifin, (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
As the center of human habitation, the city’s growing in tandem with the increase of urban population dan urban sprawl’s. The increase in urban population has created a variety of effects on space and environment. The urban space limitations urged people especially urban society to utilize their existing space as best as possible and looking at the potential to reused the contaminated natural resources. In the other hand, the urban sprawl has sparked a conflict between the settlement and the brownfill area; especially the ex-landfill site. The existence of 147 ex-landfill sites areas in the vicinity of urban settlement requires an action to restructuring of the urban planning in Malaysia. Ex-landfill sites which is synonymous with the negative impact on the environment and public perception must be redevelop immediately. Development needs of the ex-landfill site in the context of development in Malaysia are articulated in the National Urban Policy and the National Landscape Policy. Redevelopment of the ex-landfill is not only said to be able to mitigate with the environment problems, but also could improve the number of urban spaces and the urban economy. Hence, this paper argues the need for ex-landfill sites to be redeveloped as a public park or open spaces. Therefore, the planning standard of 2 hectares of open spaces per 1,000 urban populations could be achieved. The argument on the needs of redevelopment ex-landfill site as open space or Public Park will also be supported with literature data and field studies that show the effect of increasing well-being of the urban society based as the impact of the redevelopment of ex-landfill site as public park.